Characterization of Carbon Nanotube field effect transistor - Khan, Sabbir Ahmed; Hasan, Mahmudul (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.